PKM PELATIHAN PEMBUATAN BLOG DENGAN BLOGSPOT SEBAGAI SARANA INFORMASI DIGITAL - Mercy Hermawati; Dian Nur Sholihaningtias; Ade Kurnia Solihin; Akbar Muchbarak (Unity Academy, 2024)
Technology serves as a tool and support for the learning process. Following interviews at the Tali Bangs Foundation children's home, it was revealed that they had not utilized the internet, particularly blog spot, as a digital platform for sharing information. This service initiative aims to offer training to enhance the skills of high school-aged orphanage children engaged in trading activities to promote their products, information, and services through the internet. Blog spot stands out as the most user-friendly and cost-effective web medium. The training will encompass various crucial aspects of blog creation, such as selecting a theme, configuring the layout, crafting engaging content, incorporating images and multimedia, and linking with social media. Participants will be guided through practical steps to develop an appealing and functional blog. Additionally, the training will delve into marketing strategies through blogs, including search engine optimization (SEO) and the proper utilization of keywords. Participants will grasp how to leverage blog spot's potential to enhance visibility and expand their audience reach. By the end of the training, participants are expected to have a solid grasp of blog creation using Blog spot and be capable of applying the acquired knowledge and skills in the realm of digital information. As a result of this program, the trainees have established a sturdy foundation to kickstart the development of personal, business, and other types of blogs utilizing the Blog spot platform as their primary tool.